2016
DOI: 10.5897/ajmr2014.7200
|View full text |Cite
|
Sign up to set email alerts
|

Microorganisms associated with African star apple (Chrysophylum albidum) and their hydrolases

Abstract: Microorganisms associated with African star apple (Chrysophylum albidum Linn), their quality characteristics and hydrolases were investigated. The bacteria species were Bacillus cereus, B. polymyxa, Escherichia coli, Proteus mirabilis, Pseudomonas aeruginosa and Staphylococcus aureus, while the fungi species were Aspergillus flavus, A. fumigatus, A. niger, A. repens, Fusarium sp., Mucor mucedo, Trichoderma viride and Rhizopus stolonifer. Pathogenicity tests revealed that all the isolates were pathogenic on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
3
1
1
Order By: Relevance
“…The result in Table 1 agrees with the report of Oyeleke and Oyewole (2005), were microbial load were observed after analysis on spoilt Chrysophyllum albidum. The report of Arotupin et al (2016) agrees with this study were microbial loads similar to that of this study were observed. The microbes isolated from this research in Table 2 and 3 are similar with the microbes isolated from the research of Arotupin et al (2016), Oranusi et al (2015), Oyeleke and Oyewole (2005).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The result in Table 1 agrees with the report of Oyeleke and Oyewole (2005), were microbial load were observed after analysis on spoilt Chrysophyllum albidum. The report of Arotupin et al (2016) agrees with this study were microbial loads similar to that of this study were observed. The microbes isolated from this research in Table 2 and 3 are similar with the microbes isolated from the research of Arotupin et al (2016), Oranusi et al (2015), Oyeleke and Oyewole (2005).…”
Section: Resultssupporting
confidence: 93%
“…The report of Arotupin et al (2016) agrees with this study were microbial loads similar to that of this study were observed. The microbes isolated from this research in Table 2 and 3 are similar with the microbes isolated from the research of Arotupin et al (2016), Oranusi et al (2015), Oyeleke and Oyewole (2005). The presence of these microbes could be because of the rich nature of the fruit, therefore supporting the growth and proliferation of these organisms.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…This is in agreement with the report of Akinyosoye and Arotupin [23] stating that bacterial are most numerous organism in the soil. The high counts of bacteria, mould and yeast in the plantain fruits during fermentation may be due to the high concentration of nutrients which agrees with the findings of Arotupin et al [24] that arrays of microorganisms could increase in population due to the nutrient rich nature of the substrate, thus, supporting the growth and proliferation of microorganisms. Low pH could be responsible for the increased fungal population [25].…”
Section: Discussionsupporting
confidence: 88%
“…Nasrin attested to this when combination of molasses and jackfruit were used as a substrate for mutant strain of A. niger for citric acid production [34]. The high counts of bacteria, mould and yeast in the millet cobs during degradation may be due to the high concentration of nutrients which agrees with the findings of Arotupin that arrays of microorganisms could increase in population due to the nutrient rich nature of the substrate, thus, supporting the growth and proliferation of microorganisms [35]. Low pH could be responsible for the increased fungal population [36].…”
Section: Discussionmentioning
confidence: 52%